Application of MOF-5 derived two-dimensional carbon-based nanosheet material as matrix in MALDI (matrix-assisted laser desorption ionization)

By derived the MOF-5 as a two-dimensional carbon-based nanocrone material C-MOF-5, and as a matrix in Maldi, the problem of decline Efficient small molecular detection and salt resistance extended the life of the detector.

CN119355105APending Publication Date: 2025-01-24CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500333.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional organic small molecule matrix will have strong ontological peak signals in low-mass regions (m/z < 500 Da), hindering the ability of MALDI-MS in small-mass molecular determination, and it is difficult to obtain uniform co-crystalline samples, resulting in signals The detection effect is poor, especially in high-salt environments, the ionization effect of the substance to be tested is reduced.

Method used

The MOF-5-derived two-dimensional carbon-based nanocrite material is used as a matrix, and the C-MOF-5 material is formed by the high-temperature carbonization MOF-5 under the N2 atmosphere. Excellent chemical stability.

Benefits of technology

The C-MOF-5 as a substrate has low laser energy threshold and high-resolution absorption efficiency in Maldi, which can effectively detect small molecular analysis materials, especially sugar, and has good salt resistance, extending the life of the detector.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355105A_ABST
    Figure CN119355105A_ABST
Patent Text Reader

Abstract

The invention discloses an application of an MOF-5 derived two-dimensional carbon-based nanosheet material as a matrix in MALDI (matrix-assisted laser desorption ionization). The prepared two-dimensional MOF-5 nanosheet is heated for 6 hours at the high temperature of 550 DEG C in the N2 atmosphere to become the MOF-5-derived two-dimensional carbon-based nanosheet material (C-MOF-5), part of the pore structure and structural characteristics of original MOF are reserved, and the MOF-5-derived two-dimensional carbon-based nanosheet material has more excellent chemical stability compared with a conventional carbon material. The C-MOF-5 derived two-dimensional carbon-based nanosheet has the advantages of low laser energy threshold value, high desorption ionization efficiency and high salt tolerance when being used as a matrix analysis analyte. In addition, a background peak is cleaner than that of a traditional organic matrix, which is very beneficial to detection of small molecule analytes, especially has excellent performance in detection of saccharides, and the required laser capability is low. And the service life of the detector can be prolonged due to relatively low laser energy, so that the material is expected to be used as an excellent matrix of MALDI-MS.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mass spectrometry detection, and particularly relates to an application of a MOF-5-derived two-dimensional carbon-based nanosheet material as a matrix in MALDI. Background Art

[0002] In recent years, matrix-assisted laser desorption ionization (MALDI) has received increasing attention and is often used to analyze biomolecules such as proteins, peptides, DNA and polysaccharides, as well as other large organic molecules such as polymers and dendrimers. However, traditional organic small molecule matrices, such as 2,5-dihydroxybenzoic acid (DHB), α-cyano-4-hydroxycinnamic acid (CHCA), 4-hydroxy-3,5-dimethoxycinnamic acid (SA), etc., will have strong bulk peak signals in the low mass region (m / z < 500 Da), which usually hinders the ability of MALDI-MS in the determination of small mass molecules, such as glucose, fructose and other sugar molecules. In addition, using traditional organic matrices, it is sometimes difficult to obtain uniform co-crystallized samples, resulting in poor signal detection. In addition, MALDI-MS is usually used to detect biological samples, such as small molecule metabolites, and biological samples usually have a high salt environment, which will cause the traditional organic matrix to reduce the ionization effect of the analyte during MALDI mass spectrometry detection, resulting in suppression of the analyte signal.

[0003] In order to overcome the shortcomings of traditional organic matrices, nanomaterials have been developed as matrices, which have many advantages, such as low background noise in the low mass range, high loading capacity, high salt tolerance, excellent small molecule detection ability, and easy sample preparation. Among the various nanostructured materials explored as matrices in MALDI-MS, carbon-based materials have been widely studied as matrices and show very effective analyte desorption and ionization capabilities because they are easier to functionalize. However, matrices that can be used as matrices for the determination of small mass molecules in MALDI-MS are still relatively scarce, and ordinary carbon materials will form some carbon cluster ions when irradiated with high laser flux, resulting in ion suppression effect, which impairs the ion detection of the analyte.

[0004] Metal-organic framework materials (MOFs) have been widely used as matrices in MALDI MS because of their high ionization efficiency, large specific surface area, strong thermal and chemical stability, and good ultraviolet absorption performance. However, most MOFs used as matrices, such as UiO-66 and MIL-101, are three-dimensional structures with octahedral morphology, and few people focus on two-dimensional MOF nanosheets to study the performance of matrices. Common nanosheets, such as graphene, transition metal disulfides, and thin-layered metal oxides, have been widely used in the field of nanomaterials due to their excellent electronic and photonic properties and good solubility. Two-dimensional MOF nanosheets combine the characteristics of MOF and two-dimensional nanosheets and have broad application prospects in separation, sensing, and energy storage. Since the lattice structure of two-dimensional MOF nanosheets is very stable, it requires higher laser energy as a matrix to assist molecular desorption and ionization, which has adverse effects on both the instrument and the molecules to be measured, such as reducing the life of the laser and detector, and causing molecular pyrolysis or molecular discrimination. Summary of the invention

[0005] In order to overcome the shortcomings of the existing matrix, the purpose of the present invention is to provide a MOF-5 derived two-dimensional carbon-based nanosheet material as a matrix for use in MALDI.

[0006] The first aspect of the present invention provides a matrix in matrix-assisted laser desorption ionization, wherein the matrix is ​​a two-dimensional carbon-based nanosheet material derived from MOF-5. The material is a two-dimensional MOF-5 nanosheet heated at 500-700 ° C for 6-8 h in a N2 atmosphere to become a MOF-5-derived two-dimensional carbon-based nanosheet material (C-MOF-5), which not only retains a part of the pore structure and structural characteristics of the original MOF, but also has better chemical stability than conventional carbon materials.

[0007] The second aspect of the present invention provides a method for preparing the above-mentioned MOF-5 derived two-dimensional carbon-based nanosheet material, which specifically comprises the following steps: (1) Dissolving the zinc source and the organic ligand in DMF, performing a solvothermal reaction, cooling to room temperature, washing, and collecting the product by centrifugation to obtain MOF-5; (2) MOF-5 is carbonized at 500-700 °C for 6-8 h in a nitrogen atmosphere to obtain a MOF-5-derived two-dimensional carbon-based nanosheet material, denoted as C-MOF-5.

[0008] The zinc source is a soluble zinc salt such as zinc nitrate, zinc sulfate, zinc chloride and hydrates thereof.

[0009] The organic ligand is terephthalic acid (H2BDC).

[0010] The molar ratio of zinc to organic ligand is 2-3:1, preferably 2.5-3:1.

[0011] Furthermore, the solvent thermal reaction temperature of step (1) is preferably 130° C., and the reaction time is preferably 5 h.

[0012] Furthermore, the heating rate of the high temperature carbonization in step (2) is 5-10 °C / min.

[0013] Furthermore, the high temperature carbonization temperature of step (2) is preferably 550°C, and the carbonization time is 6 h.

[0014] The third aspect of the present invention provides the use of the two-dimensional carbon-based nanosheets derived from the above MOF-5 as a matrix in MALDI. The two-dimensional carbon-based nanosheets derived from C-MOF-5 after carbonization have the advantages of low laser energy threshold and high desorption ionization efficiency when used as a matrix to analyze analytes. In addition, there are cleaner background peaks than traditional organic matrices, which is very helpful for detecting small molecule analytes, especially in the detection of sugars, and the required laser energy is low. Lower laser energy can also increase the life of the detector, so it is expected to meet the requirements as an excellent matrix for MALDI-MS. This matrix can also be effectively used in the fields of mass spectrometry imaging, metabolomics, etc.

[0015] Specifically, the method of analyzing C-MOF-5 as a matrix in MALDI-MS comprises the following steps: (1) Preparation of C-MOF-5 matrix solution: Weigh 0.75 mg, 1.5 mg, 3 mg, and 5 mg of matrix powder and dissolve them in 1 mL of deionized water in a centrifuge tube to obtain a matrix solution with a matrix concentration of 0.75 mg / mL to 5 mg / mL.

[0016] (2) Prepare the sample target plate: One of the following two methods can be used: a) Sample dropping method 1: Use a pipette to draw 1 µL of matrix and drop it on the target plate. Let it stand for 10 minutes. After the matrix crystallizes on the target plate, add 1 µL of the analyte to cover the crystallization point. Let it stand for 20 minutes to form a co-crystallization of the matrix and the analyte. Then enter the instrument for sample measurement.

[0017] b) Sample drop method 2: Use a pipette to draw 5 µL of matrix into a 0.2 mL centrifuge tube, then add 5 µL of the analyte to be tested. After mixing and ultrasonication, use a pipette to draw 1 µL of the mixed solution of matrix and analyte and drop it on the target plate. Let it stand for 20 minutes to form co-crystallization of matrix and analyte, and then enter the instrument for testing.

[0018] Through experimental verification, the C-MOF-5 matrix of the present invention adopts the sample dropping method 1 to carry out the sample dropping experiment.

[0019] In some specific embodiments of the present invention, the effect of matrix concentration on mass spectrometry analysis was investigated, and the results showed that the optimal mass concentration of the matrix solution was 1.5 mg / L.

[0020] The C-MOF-5 of the present invention is used as a MALDI-MS matrix, and the concentration of the analyte solution to be detected and analyzed is 0.0001-0.01 mol / L.

[0021] Furthermore, the above C-MOF-5 was used as a MALDI-MS matrix for test analysis. When performing positive ion detection, the reflection mode was selected; the random walk selected partial sample; the laser size was selected as 2_small, and the laser energy was 10~30%; when performing negative ion detection, the linear mode was selected; the random walk selected partial sample; the laser size was selected as 2_small, and the laser energy was 1%.

[0022] Furthermore, the two-dimensional carbon-based nanosheets derived from the MOF-5 are used as a matrix to test and analyze small molecules or polymer molecules in MALDI.

[0023] Furthermore, the m / z of the small molecule substance is less than 600 Da, and the small molecule substance includes but is not limited to sugar substances such as glucose, fructose, lactose, sucrose, maltose, and raffinose.

[0024] Furthermore, the m / z of the polymer molecule is between 600-4000 Da.

[0025] Furthermore, C-MOF-5 has good salt tolerance, which is very helpful for its later application in the detection of small molecule metabolites.

[0026] The MOF-5-derived two-dimensional carbon-based nanosheet material provided by the present invention can be used as a matrix in MALDI and can be used for testing and analyzing high-salinity samples, including but not limited to testing and analyzing blood samples, tissue cell samples, microbial samples, water environments or soil environments and the like.

[0027] Furthermore, the MOF-5-derived two-dimensional carbon-based nanosheet material provided by the present invention is used as a matrix in MALDI in the fields of mass spectrometry imaging, metabolomics, environmental analysis, etc.

[0028] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention is the first to modify the two-dimensional MOF nanosheet material MOF-5 into a MOF-5-derived two-dimensional carbon-based nanosheet material, which shows a good matrix effect. This has brought new understanding and inspiration to the two-dimensional MOF for researchers in the MALDI field who use MOF as a matrix.

[0029] 2. When C-MOF-5 was used as the matrix, the concentration gradient was set to 0.75 mg / mL, 1.5 mg / mL, 3 mg / mL, and 5 mg / mL, and 1.5 mg / mL was found to be the optimal concentration.

[0030] 3. Using C-MOF-5 as the matrix, when analyzing the analyte, the salt concentration gradient was set to 0 mM, 10 mM, 100 mM, and 1000 mM, and it was found that C-MOF-5 has good salt tolerance.

[0031] 4. C-MOF-5 requires lower laser energy to detect sugars, and the laser threshold is much lower than most nanomaterials and organic matrices, so it can increase the life of the detector and extend the service life of the instrument. The high desorption ionization efficiency and cleaner background peaks are also very helpful for detecting small molecule analytes. Because it can well detect the metabolism of sugars, this matrix can also be effectively used in mass spectrometry imaging, metabolomics and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 SEM images of a) MOF-5 and b) C-MOF-5.

[0033] Figure 2 Infrared spectra of C-MOF-5 and MOF-5.

[0034] Figure 3 This is the UV-visible absorption spectrum of C-MOF-5.

[0035] Figure 4 Glucose was analyzed for MOF-5, C-MOF-5, and C-MOF-5-PVP-TEA as matrices, as well as traditional organic matrices CHCA and DHB. Where M is the corresponding analyte. Glucose (m / z = 203 Da, [M+Na] + ), glucose concentration was 0.01mol / L, and laser energy was 10%, 30% and 50%.

[0036] Figure 5 Mass spectra of glucose, fructose, lactose, sucrose, maltose, and raffinose analyzed using C-MOF-5 as a matrix; M is the corresponding analyte. Glucose (m / z = 219 Da, [M+K] +), fructose (m / z = 219 Da, [M+K] + ), lactose (m / z = 381 Da, [M+K] + ), sucrose (m / z = 381 Da, [M+K] + ), maltose (m / z = 381 Da, [M+K] + ), raffinose (m / z = 543 Da, [M+K] + ), the analyte concentration was 0.01 mol / L, and the laser energy was 10% and 25%.

[0037] Figure 6 The polymers PEG600 and PEG4000 were analyzed for C-MOF-5 as matrix; analyte concentration: 0.0001 mol / L, laser energy of 15 % and 25 %.

[0038] Figure 7 Using C-MOF-5 as the matrix, the probe molecule sodium tetraphenylborate was analyzed in negative ion mode. Where M is the corresponding analyte. Sodium tetraphenylborate (m / z = 319 Da, [M-Na] - ), the concentration of sodium tetraphenylborate was 0.001 mol / L, and the laser energy was 1%.

[0039] Figure 8 Glucose was analyzed for different concentrations of C-MOF-5 as a matrix. Where M is the corresponding analyte. Glucose (m / z = 203 Da, [M+Na] + ), glucose concentration was 0.001 mol / L, and laser energy was 20%.

[0040] Fig. 9 Using C-MOF-5 as the matrix, glucose was detected in aqueous NaCl solutions with different concentrations to verify the salt tolerance of the matrix. Where M is the corresponding analyte. Glucose (m / z = 203 Da, [M+Na] + ), glucose concentration was 0.001 mol / L, and laser energy was 20%. DETAILED DESCRIPTION

[0041] The present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention. Example 1

[0042] A method for preparing a two-dimensional carbon-based nanosheet material derived from MOF-5 comprises the following steps: (1) Mix 1.659 mmol Zn(NO3)2·6H2O and 0.633 mmol H2BDC in 13 ml DMF solvent and stir until the mixture becomes clear.

[0043] (2) The obtained mixed solution was heated to 130 °C in a reactor and reacted for 5 h; (3) After the solution is cooled to room temperature, the product is washed with DMF, acetone, methanol, ethanol, and water in sequence, and then centrifuged and vacuumed to obtain MOF-5; (4) Under N2 atmosphere, MOF-5 was carbonized at 550°C for 6 h to obtain C-MOF-5, i.e., the MOF-5-derived two-dimensional carbon-based nanosheet material. Example 2

[0044] A method for preparing a two-dimensional carbon-based nanosheet material derived from MOF-5 comprises the following steps: (1) Mix 1.659 mmol Zn(NO3)2·6H2O and 0.633 mmol H2BDC in 13 ml DMF solvent, then add 700 mg PVP and 500 μL triethylamine (TEA), and stir until the mixture becomes clear.

[0045] (2) The obtained mixed solution was heated to 130 °C in a reactor and reacted for 5 h; (3) After the solution is cooled to room temperature, the product is washed with DMF, acetone, methanol, ethanol, and water in sequence, and then centrifuged and vacuumed to obtain MOF-5-PVP-TEA; (4) Under N2 atmosphere, MOF-5 was carbonized at 550 °C for 6 h to obtain C-MOF-5-PVP-TEA. Example 3

[0046] MOF-5 was prepared according to the method of Example 1 as a control.

[0047] Figure 1 SEM images of MOF-5 and C-MOF-5. Figure 1 a) It can be seen that the MOF-5 prepared by the present invention has a two-dimensional structure. Figure 1 b) It can be seen that C-MOF-5 after high-temperature carbonization modification still retains a certain two-dimensional structure.

[0048] Figure 2 The infrared spectra of MOF-5 and C-MOF-5 are shown at a wave number of 3411 cm -1 The strong diffraction peak at 1614 cm-1 in C-MOF-5 comes from the vibration of the hydroxyl groups of adsorbed water molecules. -1 and 1377 cm-1 The absorption peaks at are caused by the antisymmetric stretching vibration and symmetric stretching vibration of C=O in the carboxyl group, indicating that it still retains some functional groups.

[0049] Figure 3 This is the UV-visible absorption spectrum of C-MOF-5. It can be seen that C-MOF-5 has an absorption peak at 354 nm, which proves that C-MOF-5 meets the laser absorption conditions as a matrix in matrix-assisted laser desorption ionization mass spectrometry.

[0050] MOF-5, C-MOF-5, and C-MOF-5-PVP-TEA were used as matrices to analyze glucose (m / z = 203 Da, [M+Na] + ), and compared with the commonly used matrix 2,5-dihydroxybenzoic acid (DHB) and α-cyano-4-hydroxycinnamic acid (CHCA) of matrix-assisted laser desorption ionization (MALDI). Specifically: Matrix first, then analyte method, weigh 1.5 mg of MOF-5, C-MOF-5 and C-MOF-5-PVP-TEA matrix powder, 10 mg of DHB and CHCA, respectively, and dissolve them in centrifuge tubes containing 1 mL of deionized water to prepare matrix solutions. Weigh the corresponding 18 mg of glucose and dissolve it in a centrifuge tube containing 10 mL of deionized water to prepare a glucose concentration of 0.01 mol / L. Set the laser energy to 10%, from Figure 4 It can be seen that the uncarbonized MOF-5 has no signal under the laser energy. Compared with the carbonized C-MOF-5 and C-MOF-5-PVP-TEA, only C-MOF-5 can detect glucose. When the laser energy of the C-MOF-5-PVP-TEA matrix is ​​increased to 50%, a detection signal peak appears, but its peak intensity is still lower than the peak intensity of C-MOF-5 under low laser energy. And DHB and CHCA both need laser energy to reach 30% to detect glucose. It can be seen that the laser threshold required for the C-MOF-5 material prepared by the present invention is much lower than most nanomaterials and organic matrices, so the life of the detector can be increased, and the service life of the instrument is extended.

[0051] Figure 5 Using C-MOF-5 as the matrix, the mass spectra of glucose, fructose, lactose, sucrose, maltose, and raffinose were analyzed respectively. It can be seen that this matrix can be used to analyze a variety of small sugar molecules. Where M is the corresponding analyte. Glucose (m / z = 219 Da, [M+K] + ), fructose (m / z = 219 Da, [M+K] + ), lactose (m / z = 381 Da, [M+K] +), sucrose (m / z =381 Da, [M+K] + ), maltose (m / z = 381 Da, [M +K] + )、raffinose(m / z =543 Da,[M+K] + ), the analyte concentration was 0.01 mol / L, and the laser energy was 10% and 25%.

[0052] Figure 6 Using C-MOF-5 as the matrix, the polymers PEG600 and PEG4000 were analyzed. The polymer concentration was 0.0001 mol / L, and the laser energy was 15% and 25%.

[0053] Figure 7 Using C-MOF-5 as the matrix, in negative ion mode, only 1% laser energy is needed to detect the probe molecule sodium tetraphenylborate, and the signal intensity can reach 10 5 , proving that C-MOF-5 has a high thermal desorption efficiency as a matrix. Where M is the corresponding analyte. Sodium tetraphenylborate (m / z = 319 Da, [M-Na] - ), the concentration of sodium tetraphenylborate was 0.001 mol / L, and the laser energy was 1%.

[0054] Figure 8 Using C-MOF-5 as the matrix, glucose was analyzed at matrix concentrations of 0.75 mg / mL, 1.5 mg / mL, 3 mg / mL, and 5 mg / mL. It can be concluded that 1.5 mg / mL is the optimal matrix concentration. Where M is the corresponding analyte. Glucose (m / z = 203 Da, [M+Na] + ), glucose concentration was 0.001 mol / L, and laser energy was 20%.

[0055] In order to investigate the salinity tolerance of C-MOF-5 when used as a matrix, glucose was dissolved in aqueous NaCl solutions with concentrations of 0 mM, 10 mM, 100 mM, and 1000 mM, and C-MOF-5 was used as a matrix to analyze glucose, e.g. Fig. 9 As shown in the figure, when the salt content is 1000 mM, C-MOF-5 can still detect the signal of glucose, which proves that C-MOF-5 has good salt tolerance as a matrix, which is helpful for effective application in fields such as metabolomics. Where M is the corresponding analyte. Glucose (m / z = 203 Da, [M+Na] + ), glucose concentration was 0.001 mol / L, and laser energy was 20%.

[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Application of a MOF-5 derived two-dimensional carbon-based nanosheet material as a matrix in matrix-assisted laser desorption ionization mass spectrometry.

2. The use according to claim 1, characterized in that: The MOF-5-derived two-dimensional carbon-based nanosheet material is obtained by carbonizing two-dimensional MOF-5 nanosheets at a high temperature of 500-700°C.

3. The use according to claim 1 or 2, characterized in that: The preparation method of the MOF-5-derived two-dimensional carbon-based nanosheet material comprises the following specific steps: (1) dissolving a zinc source and terephthalic acid in DMF, performing a solvent thermal reaction, cooling to room temperature, washing, and collecting the product by centrifugation to obtain MOF-5; wherein the molar ratio of zinc ions in the zinc source to terephthalic acid is 2.5-3:1; (2) Carbonize MOF-5 at 500-700 °C for 6-8 h in a nitrogen atmosphere to obtain MOF-5-derived two-dimensional carbon-based nanosheet material.

4. The use according to claim 1, characterized in that: The MOF-5 derived two-dimensional carbon-based nanosheet material is used as a matrix in matrix-assisted laser desorption ionization mass spectrometry in small molecule substance detection or polymer molecule mass spectrometry analysis.

5. The use according to claim 4, characterized in that: The m / z of the small molecule is less than 600 Da; the m / z of the polymer molecule is between 600-4000 Da.

6. The use according to claim 4, characterized in that: The small molecule substance is a sugar substance.

7. The use according to claim 1, characterized in that: The application method is any of the following: a) preparing a matrix solution, dropping the matrix solution on a target plate and letting it stand for crystallization, then dropping an analyte solution on the surface of the matrix, letting it stand for formation of co-crystallization of the matrix and the analyte, and then entering the instrument for mass spectrometry analysis; b) preparing a matrix solution, and uniformly mixing the matrix solution and the analyte solution to be tested in a volume ratio of 1:1 to obtain a mixed solution; dropping the mixed solution on a target plate, allowing it to stand to form co-crystallization of the matrix and the analyte, and then feeding the mixed solution into an instrument for mass spectrometry analysis.

8. The use according to claim 7, characterized in that: The mass concentration of the MOF-5 derived two-dimensional carbon-based nanosheet material in the matrix solution is 0.75-5 mg / mL; and / or the concentration of the analyte solution to be tested is 0.0001-0.01 mol / L.

9. The use according to claim 7, characterized in that: The mass spectrometry analysis includes a positive ion detection mode and a negative ion detection mode.

10. The use according to any one of claims 1 to 9, characterized in that: Used in mass spectrometry imaging, metabolomics, and environmental analysis.